2011
DOI: 10.4102/sajems.v14i3.9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Global Recession on the Work Restructuring Levels Of Managers in the South African Automotive Industry

Abstract: The aim of this investigation was to examine the work restructuring levels of managers in the South African automotive industry, and how these levels are affected by the global economic recession. Work restructuring was investigated from the perspective of the managers' work and family involvement levels. Data was gathered using a questionnaire that was emailed to automotive industry managers throughout South Africa. Results show that no significant gender differences occur for work involvement, family involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The fact that women place more importance on pay and a conducive working environment is in line with South African findings by , yet is in contrast to Chow and Ngo's (2002) study that showed that both male and female employees consider high salary and good working conditions to be important in their jobs. The finding that women place more importance on integrating their work and home lives is also in contrast to findings by Paddey and Rousseau (2011), who found no gender differences in South Africa with regards to restructuring work to accommodate one's home life such as family responsibilities. Work-family conflict can have serious implications for organisations, such as poor performance, lower levels of commitment and loyalty and an increase in employee turnover rates (Fu & Shaffer, 2001;Thornthwaite, 2004), no matter whether experienced by men or women.…”
Section: Discussioncontrasting
confidence: 55%
“…The fact that women place more importance on pay and a conducive working environment is in line with South African findings by , yet is in contrast to Chow and Ngo's (2002) study that showed that both male and female employees consider high salary and good working conditions to be important in their jobs. The finding that women place more importance on integrating their work and home lives is also in contrast to findings by Paddey and Rousseau (2011), who found no gender differences in South Africa with regards to restructuring work to accommodate one's home life such as family responsibilities. Work-family conflict can have serious implications for organisations, such as poor performance, lower levels of commitment and loyalty and an increase in employee turnover rates (Fu & Shaffer, 2001;Thornthwaite, 2004), no matter whether experienced by men or women.…”
Section: Discussioncontrasting
confidence: 55%
“…In Muller (2008:22) response to these changes, many working families have had, over the years, to reallocate and redistribute family responsibilities in order to address the needs of their children. Possibly the most significant adaptation that has taken place is the increased role that fathers now have in looking after their children (Gottfried and Gottfried 2008 as cited by Paddey and Rousseau 2011). With the emergence of these so-called 'new' or 'modern' fathers, many fathers are ''no longer mere breadwinners … but are increasingly aware of, and concerned about what they do as fathers and how they do it'' (Richter et al 2011:65).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…In order to increase the chances of such policies being successful, Paddey and Rousseau (2011) emphasise the need to develop, implement, monitor and evaluate work-family policies based on a process of collaboration and consultation with employees about their individual needs regarding the balance between their work and family lives. The post-Fordism model of 'negotiated flexibility' which allows for active union participation, flexibility to meet employee needs and a wider worker involvement is worthy of consideration in this regard.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation